Penentuan Kandungan Senyawa Hidrokuinondan Merkuri Pada Krim Pemutih Wajah di Pasar Aceh Menggunakan Metode Spektrofotometri - Erda Marniza; Resmila Dewi; Widya Angreni (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Whitening cream is a mixture of chemicals or other ingredients with the property of being able to whiten the skin or lighten black spots on the skin. Facial whitening creams contain harmful compounds such as mercury and hydroquinone. Mercury is a dangerousheavy metal that is toxic and carcinogenic to the body, while hydroquinone is a chemical compound that is included in hard drugs and used by doctors as a drug to treat hyperpigmentation. The purpose of this study was to determine the presence or absence of mercury and hydroquinone in the samples and to determine the levels of mercury and hydroquinone in face whitening creams circulating in Aceh Market. The stages of this research consisted of testing the mercury content using KI 0.5 N, determining the levels using an Atomic Absorption Spectrophotometer, testing the hydroquinone content using 1% FeCl reagent and determining the hydroquinone content using a UV-Vis spectrophotometer. The results of the research showed that of the 8 samples studied there were 4samples containing mercury, namely with levels in sample code B (5.729,20 mg/kg), C (5.692mg/kg),D (2.905mg/kg), E (104,83 mg/kg) and the 8 samples studied there were 6 samples containing hydroquinone, namely the levels in sample B (6,239ppm),C (6,890ppm),D (6,478ppm); E (10,637ppm),G (7,722ppm),H (3,638ppm).